Fish to 2020: Supply and demand in changing global markets - Delgado, Christopher L.; Wada, Nikolas; Rosegrant, Mark W.; Meijer, Siet; Ahmed, Mahfuzuddin (International Food Policy Research Institute, 2003)
While fishing must surely be one of the oldest recorded sources of livelihood, it is only comparatively recently that fish have become important components of the diets of the majority of the world’s people—especially those living in developing countries. Consumption of fish and seafood products reached 14 kilograms per capita in developing countries in 2001, nearly twice the level recorded in the early 1970s, while population in those countries doubled over the same period. Fish are an important component of the rapid growth of the consumption of animal products in developing countries over the past two decades and into the foreseeable future.